Evaluation of Anti-angiogenic Activity of Silver Nanoparticle Synthesis by Rubina tinctorum L (Ru-AgNPs) Using Chicken Chorioallantoic Membrane (CAM) Assay - Sara Ghandehari (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk, 2018)
Abstract Background: Angiogenesis occurs in physiologic (wound healing) and pathological conditions and plays an important role in tumor growth, progression and metastasis. Therefore, the inhibition of angiogenesis can be an important approach to treat cancer diseases. In recent years, the use of nanoparticles has been developed to control cancer cells and prevent tumor growth. Various studies have shown the role of nanoparticles in reducing angiogenesis and inhibition of cancer cells. So, in this study, the anti-angiogenic effect of silver nanoparticle synthesis by Rubina tinctorum L (Ru-AgNPs) on Chicken Chorioallantoic Membrane (CAM) was investigated. Materials and Methods: In an experimental study, 60 eggs were randomly divided into 6 groups including control, laboratory control and 4 treatment groups (10 eggs/group). On the second day of incubation, a window was created on the eggs. On the 8th day, the chorioallantoic membrane of samples was treated with different concentrations of nanoparticles and on the 12th day, the image was taken from all samples. Finally, the number and length of vessels on the chorioallantoic membrane and following that weight and length of the embryo from crown to squattiest were measured. Quantitative data were analyzed using LSD-test. Results: The results showed that the Ru-AgNPs significantly reduced the length and number of blood vessels in the treated groups compared to the control group. Also, the comparison of length and weight of embryos in treated samples with control group showed that the Ru-AgNPs had an inhibitory effect on the length of the embryos, but the weight did not differ significantly in the treatment with the control group. Conclusion: Considering the inhibitory effect of the Ru-AgNPs on the angiogenesis of the chorioallantoic membrane, with further studies, this compound can be used to control and inhibit pathological angiogenesis in many diseases such as cancers.